2004
DOI: 10.1016/s0002-9440(10)63327-5
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous Pulmonary Propionibacterium acnes Primes the Host in the Development of Sarcoid-Like Pulmonary Granulomatosis in Mice

Abstract: Although many cases of sarcoidosis are self-limiting with spontaneous remission, uncontrolled pulmonary granulomatosis with fibrosis produces intolerable longterm respiratory symptoms in a minority of patients. Individuals with chronic pulmonary sarcoidosis require an alternative therapy to corticosteroidal treatment because of its insufficient effectiveness. Although many researchers have considered infection as the triggering factor for this disease, the mechanisms by which the candidate causative organisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 31 publications
5
53
0
Order By: Relevance
“…injection of heat-killed P. acnes. As reported previously [26], many granulomatous lesions were developed in the liver, but not in the lungs, after immunisation with heatinactivated P. acnes and IFA ( fig. 1a and b).…”
Section: Administration Of Heat-inactivated P Acnes With Dcs Enhancesupporting
confidence: 82%
See 3 more Smart Citations
“…injection of heat-killed P. acnes. As reported previously [26], many granulomatous lesions were developed in the liver, but not in the lungs, after immunisation with heatinactivated P. acnes and IFA ( fig. 1a and b).…”
Section: Administration Of Heat-inactivated P Acnes With Dcs Enhancesupporting
confidence: 82%
“…E3), without heat-inactivated P. acnes also could induce many large granulomas in the lungs, indicating that the pulmonary granulomatosis seen in this model was mediated by immune reactions against P. acnes. NISHIWAKI et al [26] also reported that repeated immunisation with heat-killed P. acnes using complete Freund's adjuvant (CFA) induced pulmonary granulomatosis [26], although we could not reproducibly generate granulomas using similar methods with IFA. The reason for this discrepancy is not clear, but it is likely to be due to the difference in the route and dose of immunisation with heatkilled P. acnes or adjuvant.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…Sarcoidosis is thought to be caused by an abnormal, exaggerated response of the immune system. Infectious agents such as Propionibacterium acnes, Mycobacteria suspected of causing sarcoidosis (Nishiwaki et al, 2004;Hance, 1998) , but The American Thoracic Society's wide-ranging Statement on Sarcoidosis suggested that there is no clear evidence of an infectious agent causing sarcoidosis. Genetic factors such as the human leucocyte antigens (specifically HLA-DRB1) may be a predisposition for sarcoidosis (Maliark et al, 1998), but not the only cause.…”
Section: Introductionmentioning
confidence: 99%